Rediscovery of Euxinopetalum dobatorum Hoffman, 1973 (Diplopoda, Callipodida, Schizopetalidae) in Turkey - Dragan Antić; Tamara Aleksić; Jelena Milovanović; Mert Elverici (Caucasiana)
A remarkable dwarf schizopetalid, Euxinopetalum dobatorum Hoffman, 1973, is rediscovered in the Heracles Cave (type locality) in Turkey. This poorly known species is recorded after more than 50 years and is illustrated here with photographs, photomicrographs, and scanning electron micrographs, including descriptive notes and remarks. The small body size and the reduced number of body segments in Callipodida are briefly discussed, while the question about the type locality is clarified.